Five new ocellus-bearing species of the cusk-eel genus Neobythites (Ophidiidae, Ophidiiformes) from the West Pacific, with establishment of three new species groups - Uiblein, Franz; Nielsen, Jørgen G. (Zootaxa, 2023)
Five new West Pacific species of the cusk-eel genus Neobythites (Ophidiidae) from the lower shelf and upper slope of the Solomon Sea, off Okinawa, Japan, and off Fiji are described. The descriptions are based on nine specimens from three fish collections and unvouchered fresh colour photographs showing three specimens taken shortly after being caught. The new species all bear at least one ocellus on the dorsal fin, a conspicuous colour pattern consisting of a dark spot surrounded by a contrasting white or pale ring. Fifteen ocellus-bearing congeners are rather similar with at least one of the new species, requiring detailed comparisons based on a large set of morphometric, meristic, colour and otolith-shape data from over 300 specimens. To facilitate the comparisons among the 20 Neobythites species in total and the preparation of identification keys, three new taxonomic species groups, the australiensis, kenyaensis and longiventralis groups, are established. Also, the steatiticus species group which had been previously established, is slightly updated. A key for identification of each of these four groups is prepared. The most important characters for distinction among groups are the presence and number of preopercular spines, the number and position of ocelli, and pelvic-fin length. For each of the three new groups, species accounts including new species descriptions, within-group comparisons, and identification keys are prepared. For the steatiticus group, only the description of the new species, N. pako n. sp., and an updated account of the Atlantic N. monocellatus are provided, considering previously published accounts of the other seven species in comparisons with those two species and the identification key. The results are shortly discussed, emphasizing the finding of a unique ocellus structure in N. superocellatus n. sp. (australiensis species group) and the need for taxonomic studies of the remaining 10 ocellus-bearing species of Neobythites together with additional, non-ocellus-bearing congeners.